The Effects of Behavioral Economics on Tax Amnesty - NAR, Mehmet (International Journal of Economics and Financial Issues, 2015)
Evaluating the economic behaviors in terms of psychology was considered as irrational at the beginning and this situation was rejected by also many economists. However, these approaches have been exposed to heavy criticism in recent years. Especially while explaining economic behaviors, the idea supporting that psychological attributes of economic agents should be taken into consideration has come forth, and dependence of economy on human psychology has been pointed out because, it doesn’t seem possible to understand the motives behind economic behaviors in general and taxational behaviors in particular. From this point of view, the aim of this study is defining the concept of economic psychology primarily and then as the research subject, investigating the effects of psychological approaches on tax amnesty. Keywords: Behavioral Economics; Psychology; Tax Amnesty; Tax compliance; Prospect Theory JEL Classifications: D03; E03; H2